New Insights into the Impact of Human Papillomavirus on Oral Cancer in Young Patients: Proteomic Approach Reveals a Novel Role for S100A8 - Miranda-Galvis, Marisol; Carneiro Soares, Carolina; Moretto Carnielli, Carolina; Ramalho Buttura, Jaqueline; Sales de Sá, Raisa; Kaminagakura, Estela [UNESP]; Marchi, Fabio Albuquerque; Paes Leme, Adriana Franco; Lópes Pinto, Clóvis A.; Santos-Silva, Alan Roger; Moraes Castilho, Rogerio; Kowalski, Luiz Paulo; et al. (MDPI, 2023)
Human papillomavirus (HPV) infection has recently been linked to a subset of cancers affecting the oral cavity. However, the molecular mechanisms underlying HPV-driven oral squamous cell carcinoma (OSCC) onset and progression are poorly understood. Methods: We performed MS-based proteomics profiling based on HPV status in OSCC in young patients, following biological characterization and cell assays to explore the proteome functional landscape. Results: Thirty-nine proteins are differentially abundant between HPV (+) and HPV (−) OSCC. Among them, COPS3, DYHC1, and S100A8 are unfavorable for tumor recurrence and survival, in contrast to A2M and Serpine1, low levels of which show an association with better DFS. Remarkably, S100A8 is considered an independent prognostic factor for lower survival rates, and at high levels, it alters tumor-associated immune profiling, showing a lower proportion of M1 macrophages and dendritic cells. HPV (+) OSCC also displayed the pathogen-associated patterns receptor that, when activated, triggered the S100A8 and NFκB inflammatory responses. Conclusion: HPV (+) OSCC has a peculiar microenvironment pattern distinctive from HPV (−), involving the expression of pathogen-associated pattern receptors, S100A8 overexpression, and NFκB activation and responses, which has important consequences in prognosis and may guide therapeutic decisions.
Keywords: HPV; oral cancer; prognosis; proteomics; S100A8